Copper exposure disrupts ovarian steroidogenesis in human ovarian granulosa cells via the FSHR/CYP19A1 pathway and alters methylation patterns on the SF-1 gene promoter. (1st March 2022) - Yiqin, Chen; Yan, Sun; Peiwen, Wu; Yiwei, Guo; Qi, Wang; Qian, Xu; Panglin, Wang; Sunjie, Yan; Wenxiang, Wang
Graphical abstract: Highlights: Cu exposure hinders FSH binding to FSHR. Cu induces ovarian steroidogenesis disorders via the FSHR/CYP19A1 pathway. Hypomethylation on SF-1 promoter is involved in Cu-induced steroidogenesis disorders. Abstract: Information on the effects of copper on reproduction is limited. Our previous study indicated that copper induces abnormal steroidogenesis in human ovarian granulosa cells, but the underlying mechanism remains unclear. In this study, human ovarian granulosa cells were treated with multiple concentrations of copper for 24 h. After treatment, the 17-estradiol levels were significantly increased (29.83 % and 45.12 %, respectively) in the 1.0 and 2.0 μg/mL groups but decreased (23.06 % and 31.56 %, respectively) in the 20.0 and 40.0 μg/mL groups ( P < 0.05). Similar changes in the levels of FSHR, StAR, CYP11A1, CYP19A1, HSD3β1, and SF-1 were observed. The protein levels of FSHR were increased in the 2.0 μg/mL group but decreased in the 20.0 and 40.0 μg/mL groups ( P < 0.05). Moreover, copper partially reversed the FSH-induced increase in FSHR, CYP19A1 and 17-estradiol levels, and the decreased effect of the FSH receptor binding inhibitor fragment on FSHR, CYP19A1, and 17-estradiol became more apparent after adding copper. Additionally, the total methylation levels of the SF-1 promoter and DNMTs expression were significantly decreased following copper treatment. Overall, our results indicate that copper exposure induces steroidogenesis disorders via the FSHR/CYP19A1 pathway and changes DNA methylation on the SF-1 promoter in human ovarian granulosa cells.